THE EFFECT OF LEADERSHIP STYLE ON WORK PRODUCTIVITY OF EMPLOYEES IN HRD PT. BEAUTIFUL PULP AND PAPER TIPS, CIKANDE, SERANG, BANTEN - Sofiah Nur Iradawaty (Universitas Islam Lamongan, 2022)
This study aims to identify how is the relationship between leadership style and employee productivity of the HRD PT. Indah Kiat Pulp and Paper, Cikande, Serang, Banten.The research model used in this research is quantitative and descriptive. The data collection methods used include observation, questionnaires, and literature review according to research objectives. This study uses a sample of 49 employees of PT. Indah Kiat Pulp and Paper, Cikande, Serang, Banten using the saturated sample technique.from test results, it is known that the value of linear regression test for Leadership Style data on productivity data is obtained by a correlation coefficient of 0.548, it means that there is an influence between Leadership Styles on employee productivity. While the coefficient of determination of 0.300 which means the magnitude of the leading style is able to influence productivity as much as 30% while 70% is influenced by other factors not examined. Regression testing gets the regression results with the equation = 17.704 + 0.599X. The result of t-test is more than t-table (4.492>1.685) and the significance scale is 0.05, then H0 is accepted and Ha is rejected. From the significance test, it is proved that there is a positive relationship between the leadership style on employee work productivity